Nitrate contamination characteristics and health risk assessment of groundwater in the typical area of the lower Yellow River Basin - Qinghai Deng; Xiao Wu; Wenqiang Zhang; Yue Teng; Changsuo Li; Tianshuo Gu; Caiping Hu; Qingyu Xu; Xiaotian Liu; Shuai Gao (PLoS ONE, 2026)
Nitrate is a key indicator for assessing groundwater quality, and nitrate pollution in groundwater poses a threat to water security and ecological health in the Yellow River Basin. Taking the Changxiao hydrogeological unit as an example, this paper studies the characteristics, influencing factors and health risks of nitrate pollution in groundwater by using nitrate pollution index, hierarchical cluster analysis, factor analysis, Monte Carlo simulation and human health risk assessment. The results show that the average concentration of NO 3 - -N is 19.48 mg/L, with pore water exhibiting the highest levels, followed by karst water and then fissure water in terms of average concentration. The average nitrate pollution index is 3.31, and 50% of the samples are severely polluted with nitrate. The pollution is mainly distributed in densely populated areas, especially near Xiaoli Town, Guide Town and Ancheng Town. Both anthropogenic and natural factors affect the groundwater chemical field in the study area. In areas with serious nitrate pollution, the impact of human activities is particularly serious. Probabilistic health risk assessment shows that the probabilities of potential risks posed by nitrate in pore water to children and adults are 24.37% and 6.67%, respectively; and in karst water, the probabilities to children and adults are 24.83% and 3.64%, respectively. The potential risk of nitrate to adults is far less than that to children who requires special attention. According to sensitivity analysis, the concentration of nitrate is the main variable affecting health risk assessment, which should be paid attention to reduce health risks. These results provide a scientific basis for groundwater pollution control and rational water resource management in both the study area and the lower Yellow River reaches.